1995
DOI: 10.1128/aem.61.5.2037-2039.1995
|View full text |Cite
|
Sign up to set email alerts
|

Starvation- and stationary-phase-induced acid tolerance in Escherichia coli O157:H7

Abstract: Stationary phase and the starvation of log-phase cells increased the acid tolerance of Escherichia coli O157:H7 strains. Although the degree of acid tolerance varied, the survival of most O157:H7 strains exceeded that of other, related, pathogens in a synthetic gastric fluid. Escherichia coli O157:H7 is recognized as an important cause of hemorrhagic colitis and hemolytic uremic syndrome that is disseminated by foods, water, and person-to-person contact (13). Although ground beef has been implicated as the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(95 citation statements)
references
References 26 publications
3
89
0
3
Order By: Relevance
“…At the stationary phase, several bacteria exhibit a higher level of resistance to low pH, high temperature, high osmolarity and oxidative stress than the exponential phase cultures. Results from several laboratories have shown that the acid resistance in E. coli O157:H7 is much higher in the stationary phase than in the exponential phase [8,23]. Similar observations have also been made in Shigella [9], Salmonella [24] and Listeria [25].…”
Section: E¡ects Of Growth Phase On Cell Density Dependent Acid Sensitsupporting
confidence: 61%
“…At the stationary phase, several bacteria exhibit a higher level of resistance to low pH, high temperature, high osmolarity and oxidative stress than the exponential phase cultures. Results from several laboratories have shown that the acid resistance in E. coli O157:H7 is much higher in the stationary phase than in the exponential phase [8,23]. Similar observations have also been made in Shigella [9], Salmonella [24] and Listeria [25].…”
Section: E¡ects Of Growth Phase On Cell Density Dependent Acid Sensitsupporting
confidence: 61%
“…Therefore, decreased heat tolerance may occur due to the reduced melting point of unsaturated fatty acids within the cell membrane. Other scientist have also indicated that the stress response of bacteria to sublethal environmental stresses such as changes in temperature, starvation, or high osmolarity may provide cross-protection to a variety of postphysical and postchemical stresses including heat and acid (Allen, Lepp, McKellar, & Griffiths, 2010;Arnold & Kaspar, 1995;Erdoğrul, Erbilir, & Toroğlu, 2006;House et al, 2009;Jeong, Baumler, & Kaspar, 2006;Lange & Hengge-Aronis, 1994;Leenanon & Drake, 2001;Nair & Finkel, 2004).…”
Section: Effect Of Ph and Thermal Stress On The Thermal Tolerance Omentioning
confidence: 99%
“…have been extensively studied and reported. Initial investigations carried out on bacteria such as Escherichia coli (Arnold and Kaspar 1995;Poirier et al 1998), Salmonella spp. (O'Driscoll et al 1996Mattick et al 2000Mattick et al , 2001 and Listeria spp.…”
Section: Introductionmentioning
confidence: 99%